2015
DOI: 10.1111/1462-2920.12756
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and genetic interactions between cyanobacteria and viruses in a low‐oxygen mat community inferred through metagenomics and metatranscriptomics

Abstract: Metagenomic and metatranscriptomic sequencing was conducted on cyanobacterial mats of the Middle Island Sinkhole (MIS), Lake Huron. Metagenomic data from 14 samples collected over 5 years were used to reconstruct genomes of two genotypes of a novel virus, designated PhV1 type A and PhV1 type B. Both viral genotypes encode and express nblA, a gene involved in degrading phycobilisomes, which are complexes of pigmented proteins that harvest light for photosynthesis. Phylogenetic analysis indicated that the viral-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 86 publications
1
54
0
Order By: Relevance
“…EC had one unclassified cyanobacterial ribotype that accounted for 10.5% of cyanobacterial sequences, which was not detected at the other 2 sites. The sequences of the dominant Phormidium and Planktothrix ribotypes were 100% identical to the dominant genotypes of these populations identified in previous metagenomic studies of MIS (Voorhies et al 2012(Voorhies et al , 2016.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…EC had one unclassified cyanobacterial ribotype that accounted for 10.5% of cyanobacterial sequences, which was not detected at the other 2 sites. The sequences of the dominant Phormidium and Planktothrix ribotypes were 100% identical to the dominant genotypes of these populations identified in previous metagenomic studies of MIS (Voorhies et al 2012(Voorhies et al , 2016.…”
Section: Resultssupporting
confidence: 64%
“…The dominant cyanobacteria contain genes for breakdown of phycobilisomes, consistent with regulation of phycobilisome content for optimization of photosynthetic performance and/or nitrogen homeostasis (de Vries & Ripley 2014). Associated viruses also contain this gene, suggesting that community interactions can also influence pigment content (Voorhies et al 2016).…”
Section: Physical Differences Of Study Sites Influence Mat Photophysimentioning
confidence: 99%
“…The absence of macroscopic grazing animals from the MDV lakes (Cathey et al, 1981) is consistent with low grazing pressure, though the feeding habits of the tardigrades, nematodes and protists that are present are not known. Viruses are, however, known from the water columns of MDV lakes (S€ awstr€ om et al, 2008) and have been reported from Arctic mat communities (Varin et al, 2010) and Phormidium-dominated microbial mats in other regions (Voorhies et al, 2015). It must be expected that viruses and microinvertebrates play a role in cyanobacterial turnover in Lake Hoare, though the apparent longevity of cyanobacteria suggests that this may be a minor effect.…”
Section: Discussionmentioning
confidence: 99%
“…Under some conditions, phage escape mutants can be readily picked up under laboratory conditions (68,224,225), and metagenomics data show that escape phage can increase in abundance in vivo (226)(227)(228). These associated mutations are typically located in a confined sequence area: either in the PAM sequence or in the adjacent seed sequence (68,225,229).…”
Section: Figmentioning
confidence: 99%